POTENSI KANDUNGAN ANTIOKSIDAN JAHE UNTUK MENGATASI STRES OKSIDATIF PADA IBU HAMIL DENGAN PREEKLAMSIA DAN INTRAUTERINE GROWTH RESTRICTION (IUGR): SYSTEMATIC LITERATURE REVIEW - Salsabila, Alya; Amelia, Yulan; Sofiyanti, Santi; Widiawati, Ida; Fadilah, Lola Noviani; Ferina, Ferina; Widaningsih, Neneng (Poltekkes Kemenkes Bandung, 2022)
Oxidative stress known as the key characteristics of Intrauterine Growth Restriction (IUGR) and preeclampsia, this condition occur due to the accumulation of ROS and an imbalance of the ROS and the endogene antioxidant at the early stage of pregnancy. Many studies showed that Ginger contains antioxidants which potentials to reduce the oxidative stress state. The aim of this systematic review was to explore the potential antioxidant content of ginger to reduce oxidative stress in pregnant women with preeclampsia and IUGR. 19 articles was obtained through the Google Scholar, PubMed, and Science Direct search engines using pregnancy, stress oxidative, IUGR, Preeclampsia and ginger as the keywords and five articles was chosen which were suitable with the inclusion and exclusion criteria. The articles was analyzed using PICO. The results of the analysis show that the five articles have a level of evidence II B with experimental methods and can answer problems. Analysis of the five articles found that ginger contains antioxidants, especially gingerols and flavonoids which have the potential to overcome oxidative stress in pregnant women with preeclampsia and IUGR. The analysis of the seven articles indicates that ginger contains antioxidants, particularly gingerol and flavonoids, which have the potential to address oxidative stress in pregnant women with preeclampsia and IUGR (intrauterine growth restriction). Ginger could be a solution to address or prevent preeclampsia and IUGR, which are characterized by oxidative stress.